IMPLEMENTATION OF RISK MANAGEMENT FOR OUTCOME-BASED LEARNING - Muhammad Rosiawan; Juliani Dyah Trisnawati (JURNAL EDUSCIENCE, 2023)
This classroom action research discusses the application of risk management in delivering results-based learning. The author uses a conceptual model development approach and examples of application in a course. This research is essential to guide the teaching team in conducting risk management to achieve learning outcomes by developing conceptual models. The study results show that the teaching team that carries out risk management in the learning process can guarantee more in achieving Graduate Learning Outcomes and Course Learning Outcomes. Furthermore, the teaching team continuously improves learning outcomes through the Plan-Do-Check-Act (PDCA) cycle. This conceptual model's development helps teaching staff identify, assess, evaluate, and control risks and enhance learning objectives.Keywords: Risk management; Outcome-based learning; PDCA cycle; Continuous improvement. Abstrak Penelitian tindakan kelas ini membahas penerapan manajemen risiko dalam penyampaian pembelajaran berbasis hasil. Penulis menggunakan pendekatan pengembangan model konseptual dan contoh penerapan di sebuah mata kuliah. Penelitian ini penting untuk memandu bagaimana tim pengajar menerapkan manajemen risiko untuk pencapaian hasil belajar melalui pengembangan model konseptual. Hasil penelitian menunjukkan bahwa tim pengajar yang melakukan manajemen risiko di proses pembelajaran dapat lebih menjamin dalam pencapaian Capaian Pembelajaran Lulusan dan Capaian Pembelajaran Mata Kuliah. Selanjutnya, tim pengajar melakukan peningkatan capaian pembelajaran secara berkelanjutan melalui siklus Plan-Do-Check-Act (PDCA). Pengembangan model konseptual ini bermanfaat memandu staf pengajar dalam mengidentifikasi, menilai, mengevaluasi, dan pengendalian risiko serta peningkatan tujuan pembelajaran.Kata Kunci: Manajemen risiko; Pembelajaran berbasis hasil; siklus PDCA; peningkatan berkelanjutan